PLANETARY GEARBOX 5R1 - Gorshkova, Oksana; Nekrasov, Vladimir (Revista Inclusiones, 2020)
The invention relates to transport engineering, transport machines transmission, ground-based transportation system including transport-process machines, automobiles, tractors, etc. The transmission unit currently used in domestic and foreign automobiles - the gearboxes with stepwise change of gear ratios - are characterized by the volumetric sizes and increased metal consumption. Among all types of manual transmissions, the planetary gear trains of small sizes and mass meet the requirements of reduction in machines metal consumption best of all. This is due to the effect of multithreading and the use of internal toothing. The study, systematization, analysis, synthesis of literature, materials of patent search on the problem under consideration, analysis of the research subject, comparison and grouping of theoretical material on the research problem made it possible to design and simulate the planetary gearbox 5R1.